ASSESSMENT TO IMPROVE READING COMPREHENSION - Tri Setianingsih (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2016)
Reading comprehension is important skill to acquire information and knowledge from any kind sources. Difficulties in reading comprehension for students in learning English as EFL/ESL has forced teacher to apply appropriate principles and strategies. One strategy that believed can help to solve the problem in reading comprehension is assessment. Four Roles Model can be adapted for assessment and used as a framework to address the complex nature of reading comprehension difficulties by considering the reader as: (a) a code-breaker, (b) a text-participator, (c) a text-user, and (d) a text-analyser. Breaking the code emphasised decoding of the words, and encoding of information, understanding the conventions of written, spoken, and visual multimodal texts by recognising and using the surface features of print. There are two kinds table of assessment. Table 1 presents a flexible reading comprehension assessment matrix showing the four roles of the reader with the before, during and after reading phases. Table 2 shows the elements within the matrix can be adjusted to reflect appropriate items suited for different stages of reading development or with a particular focus in mind.